Pengaruh Teknik Pengemasan dan Jenis Kemasan terhadap Umur Simpan Pendap sebagai Makanan Khas Bengkulu - Hesti Nur'aini; Nadiya Teti Aprilia; Methatias Ayu Moulina (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Pendap is one of many traditional foods from Bengkulu, more specifically from South Bengkulu Regency. As a traditional food that has long been enjoyed by the people of South Bengkulu, pendap can now be easily found in several locations in Bengkulu City, the capital of Bengkulu Province. However, like many other souvenirs that are popular with tourists visiting Bengkulu, pendap is prone to spoilage during long-distance travel. The characteristics of pendap, which is made from wet ingredients, cause it to spoil easily during long journeys. This study aims to analyze packaging techniques that can extend the shelf life of pendap as a specialty food of South Bengkulu that is widely sold in Bengkulu City. The treatments tested in this study included packaging types consisting of polypropylene (PP), polyethylene (PE), and aluminum polypropylene (Al-PP) plastic, using vacuum and non-vacuum packaging techniques. The following tests were conducted: pH analysis, moisture content analysis, total plate count (TPC) analysis, and organoleptic testing. The results of the study showed that packaging techniques and packaging types greatly affect the shelf life of pendap. It was found that among the various packaging types and packaging techniques tested in the study, the vacuum technique with polyethylene (PE) plastic packaging provided a longer shelf life than the others, with a shelf life of 6 days.